A STRUGGLE FOR SAVING THE WORLD BY CAPTAIN STEVEN HILLER IN INDEPENDENCE DAY MOVIE: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - WIDYANINGRUM , DIAN (2010)
The major problem of this study is to reveal the struggle of saving the world by Steven Hiller reflected in Independence Day movie. The objectives of the study are; to analyze the structural elements of the movie and to analyze the character of Steven Hiller based on individual psychological analysis.